Pest categorisation of Longidorus diadecturus. (15th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of Longidorus diadecturus (Nematoda: Longidoridae) for the EU. The nematode is a well‐defined taxon and was described from Ontario, Canada and later reported from some states in the USA. The nematode is not present in the EU. It is regulated by Council Directive 2000/29/EC, listed in Annex I A I as L. diadecturus Eveleigh and Allen. It is a migratory ectoparasitic nematode species puncturing cells of plant roots thereby able to transmit the nepovirus Peach rosette mosaic virus (PRMV). The pest is found in soil associated with plant species belonging to different families. L. diadecturus is able to cause direct damage to plants, but its main damage is caused by vectoring PRMV. Soil is a potential pathway for this nematode for entry into the EU. The nematode is able to survive adverse conditions, but the virus may not persist inside the nematode for extended periods. Climatic conditions in the EU are similar to those found in the countries where the pest is currently present. Hosts of the nematode (and the associated virus) are, e.g. peaches and grapes; those crops are also widely cultivated in the EU. The nematode only moves short distances (around 1 m) but may be spread with soil moving activities. Measures are available to inhibit entry via soil as such. Entry of the nematode with soil attached to plants for planting that are not regulated is possible. L. diadecturus does satisfy all the criteria that are within the remit of EFSA to assess to be regarded as a potential Union quarantine pest.